Становлення професійної компетентності продуцентів радіопрограм духовної тематики в українській еміграції - Гиріна, Тетяна Сергіївна (Класичний приватний університет, 2022)
Мета статті – осмислити аспект релігійного радіомовлення в структурі радіопрограм української еміграції в радіопросторі зарубіжних країн у ХХ ст. Методологія дослідження ґрунтується на використанні загальнонаукових методів опрацювання архівів (оцифрованих чисел українського щоденника «Свобода» у 1935–1991 рр., досяжних у вільному доступі), моніторингу виявлених згадок про присутність українськомовних програм у радіопросторі різних країн, кліпінгу та сортування за визначеними параметрами року, автора, назви програми, її періодичності, назви радіостанції, в ефірі якої були досяжні випуски, зони охоплення нею слухачів, характеристики, посилання на джерело інформації та її автора тощо, історіографічного, систематизації, дедуктивного та методу спостереження.

The purpose of the article is to comprehend the aspect of religious radio broadcasting in the structure of radio programs of Ukrainian emigration in the radio space of foreign countries in the twentieth century. The research methodology is based on the use of general scientific methods of archival research (digitized issues of the Ukrainian daily «Svoboda» in 1935–1991 available in free access), monitoring of identified mentions of the presence of Ukrainian-language programs in the radio space of different countries, clipping , the names of the program, its periodicity, the name of the radio station on which the broadcasts were available, the areas covered by it, characteristics, references to the source of information and its author, etc., historiographical, systematization, deductive and method of observation. Results. As a result of the research, the orientation of Ukrainians to spiritual practices and religious themes in the radio space of foreign countries was stated. The founders of the programs for Ukrainian believers were representatives of various religious organizations in North and South America, Europe and even Australia. Based on the capabilities of the organizers, the programs were created on a regular basis, and broadcast on a permanent broadcast network, as well as non-periodic holidays and annual anniversaries. Priests and members of their families became the authors and hosts of such programs. The team of radio amateurs included a treasurer who was responsible for collecting and rationally using funds donated by the community and provided by the flock to support the presence of the Ukrainian word of God in the radio space. Some programs, such as Evangelical Morning, a project of Ukrainian Baptists in North America, were briefly spread to Soviet Ukraine, from where they received grateful feedback from underground listeners. The main religious holidays were timed to broadcast the Divine Liturgy, for the sick, those who do not have the opportunity to join the action in person. Novelty. For the first time in the scientific discourse the achievements of the spiritual and religious segment of the radio programs of the Ukrainian emigration in the XX century are comprehended. The practical significance of the research results is the introduction of documented data on the state of development, achievements and thematic, genre diversity, musical diversity and polyphony of Ukrainian radio programs on the spiritual life of Ukrainians in different countries.
Keywords: українськомовна радіопрограма; Радіо Служба Божа; радіоефір; релігійна радіопрограма; світове українське радіо; Ukrainian-language radio program; Radio Service of God; radio broadcast; religious radio program; world Ukrainian radio